PHONEMES AND INTONATION AS DETERMINANTS OF SEMANTIC VARIATION IN ARABIC: A SEMANTIC ANALYSIS OF THE QUR’ANIC TEXT - Pawestri Hayuningtyas; Agustiar (Universitas Islam Negeri Palopo, 2026)
This study highlights how phonemes and intonation interact in shaping meaning variation in Arabic, emphasizing the integration of segmental and suprasegmental aspects within semantic analysis. Using a qualitative descriptive-analytical approach, the study examines selected Qur’anic texts containing phonemic and intonational variations that influence meaning. The findings reveal that phonemes significantly distinguish lexical meaning through systematic sound changes, particularly gemination, while intonation directs meaning at the utterance level by transforming interrogative forms into expressions of emphasis, warning, or affirmation. The study also demonstrates that phonemes and intonation function integratively in constructing dynamic and contextual meanings. These findings confirm that meaning variation in Arabic is determined not only by lexical structure but also by the interaction between phonological and intonational elements. Therefore, an integrative semantic approach is essential for achieving a more comprehensive understanding of meaning in Arabic language studies. تسعى هذه الدراسة إلى إبراز التفاعل بين الفونيمات والتنغيم في تشكيل تنوع الدلالة في اللغة العربية، مع التأكيد على أهمية التكامل بين الجوانب المقطعية وفوق المقطعية في إطار التحليل الدلالي. واعتمدت الدراسة المنهجَ الكيفيَّ بالأسلوب الوصفي التحليلي، من خلال تحليل نصوص قرآنية مختارة تتضمن تنوعات فونيمية وتنغيمية تؤثر في المعنى. وأظهرت النتائج أن الفونيمات تؤدي دورًا بارزًا في التمييز بين المعاني المعجمية عبر التغيرات الصوتية المنتظمة، ولا سيما ظاهرة التشديد، في حين يسهم التنغيم في توجيه المعنى على مستوى الخطاب من خلال تحويل الأساليب الاستفهامية إلى دلالات التوكيد أو التحذير أو التقرير. كما كشفت الدراسة أن الفونيمات والتنغيم يعملان في تكامل وظيفي في بناء معانٍ ديناميكية وسياقية. وتؤكد هذه النتائج أن تنوع المعنى في العربية لا يتحدد من خلال البنية المعجمية وحدها، بل يتشكل أيضًا عبر التفاعل بين العناصر الصوتية والتنغيمية. ومن ثَمَّ، تغدو المقاربة الدلالية التكاملية ضرورةً لا غنى عنها لتحقيق فهم أكثر شمولًا للمعنى في الدراسات اللغوية العربية